What makes it rain? : the story of a raindrop - Brandt, Keith, 1949-; Miyake, Yoshi (Mahwah, N.J. : Troll Associates, 1982)
Follows the journey of a raindrop through the water cycle and briefly discusses the characteristics and importance of water.
Keywords: Rain and rainfall -- Juvenile literature; Rain and rainfall; Water; Hydrologic cycle